The Role of Financial Inclusion in the Industrial World - Faris Ramadhan; Robin Robin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines the multifaceted impact of financial inclusion on industrial societies, focusing on its role in economic growth, social equity, digital transformation, and industrial development. Using a mixed-method approach combining systematic literature review and case studies from five industrial countries (Germany, South Korea, the United States, China, and Brazil), we analyze the mechanisms through which financial inclusion influences societal outcomes. Our findings reveal that financial inclusion significantly contributes to economic growth, with a 10% increase in inclusion indicators associated with a 0.2-0.7% rise in GDP growth rates. Moreover, we identify synergistic effects between financial inclusion and digital transformation, notably in mobile banking adoption. The study also highlights persistent challenges, including urban-rural divides and gender disparities in financial access. Cross-cutting themes emerge, emphasizing the importance of integrated policy approaches, regulatory innovation, and public-private partnerships in advancing financial inclusion. These insights offer valuable guidance for policymakers and financial institutions in designing effective strategies to leverage financial inclusion for sustainable and equitable economic development in industrial contexts.